Management of Anxiety and Depressive Disorders in Patients ≥ 65 Years of Age by Homeopath General Practitioners versus Conventional General Practitioners, with Overview of the EPI3-LASER Study Results - Danno, Karine; Duru, Gérard; Vetel, Jean Marie (Homeopathy, 2018)
Background The increasing use of psychotropic drugs to treat anxiety and depressive disorders (ADDs) is concerning. According to the study, ‘Etude Pharmacoépidémiologique de l'Impact de Santé Publique des modes de prise en charge pour 3 groupes de pathologies’ (EPI3)-LASER, adult ADD patients who consult a general practitioner prescribing homeopathic medicines (GP-Ho) report less psychotropic drug use and are marginally more likely to experience clinical improvement than those receiving conventional care. We determined whether these observations also apply to patients ≥ 65 years old in the EPI3 cohort.Methods The EPI3-LASER study, conducted in France between March 2007 and July 2008, was a nationwide, observational survey of the three most common reasons for primary care consultation, including ADD, and the impact of the GPs' prescribing preferences: homeopathy (GP-Ho), conventional medicines (GP-CM) or mixed prescriptions (GP-Mx). This sub-analysis included 110 patients ≥ 65 years old with ADD from the EPI3 cohort who consulted either a GP-CM or GP-Ho. Socio-demographic and medical data and details of any medications prescribed were collected at inclusion. Information regarding the patients' functional status (Hospital Anxiety and Depression Scale [HADS)]) was obtained via a telephone interview 72 hours after inclusion, and at 1, 3 and 12 months post-inclusion. Medication use and outcome were determined over the 12-month period. Differences between the GP-CM and GP-Ho groups were assessed by multivariate logistic regression analysis.Results One hundred and ten patients were recruited and 87 (79.1%) with ADD (HADS ≥ 9) at the 72-hour interview were evaluated (age range: 65–93 years, 82.8% female). Patients who consulted a GP-Ho were more likely (odds ratio [OR] = 10.38, 95% confidence interval [CI]: 1.33–81.07) to have clinical improvement (HADS < 9) after 12 months than those in the GP-CM group. Patients who consulted a GP-Ho reported less psychotropic drug use (OR = 22.31 [95% CI: 2.20–226.31]) and benzodiazepine use (OR = 60.63 [95% CI: 5.75–639.5]) than GP-CM patients.Conclusions Management of ADD patients aged ≥ 65 years by GP-Ho appears to have a real public health interest in terms of effectiveness and lower psychotropic drug use.
Keywords: anxiety; benzodiazepines; depression; patients ≥ 65 years; psychotropic drugs; homeopathy